2019
DOI: 10.1002/jac5.1137
|View full text |Cite
|
Sign up to set email alerts
|

Consumer awareness and utilization of clinical services, and their satisfaction and loyalty with community pharmacies: Analysis of a US nationwide survey

Abstract: Introduction Community pharmacies are the most accessible health care service locations. While providing greater patient health care access, there is a need for understanding consumer awareness and utilization of pharmacy‐provided services and their satisfaction and loyalty to the pharmacy setting. Objectives To determine consumer utilization and awareness of services and to identify what factors influence satisfaction and loyalty within a community pharmacy. Methods A 30‐minute online survey of 9202 adult con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…It has been reported that patients’ awareness and expectations can significantly influence patients’ health outcomes [ 30 ]. Understanding and managing patients’ awareness and expectations may also lead to increased satisfaction with healthcare services [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that patients’ awareness and expectations can significantly influence patients’ health outcomes [ 30 ]. Understanding and managing patients’ awareness and expectations may also lead to increased satisfaction with healthcare services [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marketing a program is important because many patients are not aware of the services their community pharmacy offers. 42 , 43 , 44 Such marketing strategies have been successful in similar studies and bridge the divide between the pharmacy and their patients. 36 , 41 , 45 , 46 Finally, participants shared that documentation was another strategy for successful adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Participants discussed the need for staff engagement for successful adoption of Med Sync, which has been identified as essential for implementing clinical services. 33 , 40 , 42 Also, participants acknowledged the importance of non-pharmacist staff members including pharmacy technicians, cashiers, and delivery drivers. For instance, pharmacy technicians have been identified as key players in supporting Med Sync programs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, patients may lack a general awareness of any services provided in community pharmacies outside of medication dispensing. In a recent survey by Parker and colleagues, 89% of consumers surveyed ( n = 9202) were aware pharmacies offered prescription ordering by phone or internet, but only 8% were aware that pharmacies also offer health screenings [ 43 ]. These factors may help explain why nearly 80% of our participants were not interested in making an appointment for preconception care services at the community pharmacy.…”
Section: Discussionmentioning
confidence: 99%